(untitled) (JS (JURNAL SEKOLAH), 2022)
Abstract: The Effect of Flipped Classroom Learning Model on Student Participation in Economics at SMA Negeri 1 Bandar Pulau. The purpose of this study was to determine the difference between student participation in learning using the flipped classroom learning model and student participation in learning using conventional learning models in economics subjects at SMA Negeri I Bandar Pulau class XI IPS for the academic year 2021/2022. This type of research is descriptive research. The population in this study were all students of class XI IPS SMA Negeri 1 Bandar Pulau which consisted of 2 classes, namely XI IPS 1 and XI IPS 2, totaling 71 students. Sampling in this study was carried out by total sampling where class XI IPS 1 as an experimental class using the flipped classroom learning model and class XI IPS 2 as a control class using a conventional learning model. The techniques used in data collection are observation, questionnaires and documentation. The data analysis method used is the normality test, the homogeneity of variance test and the research hypothesis test. The results of this study indicate that student learning participation after using the flipped classroom learning model on monetary policy and fiscal policy material increases when compared to using conventional learning models. This can be seen from the average value of student learning participation using the flipped classroom learning model with the result = 3.081 in the good category. Keywords: flipped classroom; learning participation; learning model Abstrak: Pengaruh Model Pembelajaran Flipped Classroom Terhadap Partisipasi Belajar Siswa Pada Mata Pelajaran Ekonomi di SMA Negeri 1 Bandar Pulau. Tujuan penelitian ini adalah untuk mengetahui perbedaan partisipasi belajar siswa yang menggunakan model pembelajaran flipped classroom dengan partisipasi belajar siswa yang menggunakan model pembelajaran konvensional pada mata pelajaran ekonomi di SMA negeri I Bandar Pulau kelas XI IPS tahun ajaran 2021/2022. Jenis penelitian ini merupakan penelitian eksperimen. Populasi dalam penelitian ini adalah seluruh siswa kelas XI IPS SMA Negeri 1 Bandar Pulau yang terdiri dari 2 kelas yaitu XI IPS 1 dan XI IPS 2 yang berjumlah keseluruhan 71 orang siswa. Pengambilan sampel dalam penelitian ini dilakukan dengan total sampling yang dimana kelas XI IPS 1 sebagai kelas eksperimen dengan menggunakan model pembelajaran flipped classroom dan kelas XI IPS 2 sebagai kelas kontrol dengan menggunakan model pembelajaran konvensional. Teknik yang digunakan dalam pengumpulan data yaitu observasi, angket dan dokumentasi. Metode analisis data yang digunakan adalah uji normalitas, uji homogenitas varians dan uji hipotesis penelitian. Hasil penelitian ini menunjukkan bahwa partisipasi belajar siswa setelah menggunakan model pembelajaran flipped classroom pada materi kebijakan moneter dan kebijakan fiskal meningkat jika dibandingkan dengan menggunakan model pembelajaran konvensional. Hal ini dapat dilihat dari nilai rata-rata partisipasi belajar siswa dengan menggunakan model pembelajaran flipped classroom dengan hasil = 3,081 dengan kategori baik. Kata Kunci: flipped classroom, partisipasi belajar, model pembelajaran